1988
DOI: 10.1007/bf00028838
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of electron acceptors with thylakoids from halophytic and non-halophytic species

Abstract: Thylakoid membranes isolated from halophytic species showed differences in their interactions with ionic and lipophilic electron acceptors when compared to thylakoids from non-halophytes. FeCN was considerably less efficient as electron acceptor with halophyte thylakoids, supporting much lower rates of O2 evolution and having a lower affinity. FeCN accepted electrons at a different, DMMIB insensitive, site with these thylakoids. 1,4-Benzo-quinones with less positive midpoint potentials were less effective in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The differences in quinones can largely be summarized by electrophilicity. Taking PPBQ, DCBQs and 2,6-DMBQ as examples and the midpoint potentials (Q/QH 2 ) at pH 7 that have been reported in the literature ( Scheme 1 ), 37 , 51 , 52 we can find a general trend in electrophilicity according to a higher E °′ value: 53 DCBQs, PPBQ, and DMBQ (from highest to lowest). Thus, DCBQs are more able to react with nucleophiles than PPBQ, which exhibits better partitioning into membranes and may quench chlorophylls directly (because this phenomenon occurs within membranes, i.e.…”
Section: Resultsmentioning
confidence: 65%
“…The differences in quinones can largely be summarized by electrophilicity. Taking PPBQ, DCBQs and 2,6-DMBQ as examples and the midpoint potentials (Q/QH 2 ) at pH 7 that have been reported in the literature ( Scheme 1 ), 37 , 51 , 52 we can find a general trend in electrophilicity according to a higher E °′ value: 53 DCBQs, PPBQ, and DMBQ (from highest to lowest). Thus, DCBQs are more able to react with nucleophiles than PPBQ, which exhibits better partitioning into membranes and may quench chlorophylls directly (because this phenomenon occurs within membranes, i.e.…”
Section: Resultsmentioning
confidence: 65%
“…In halophytic algae, benzoquinone accepts electrons from the plastoquinone pool and from a site near QB (Preston and Critchley 1988). In Fig.…”
mentioning
confidence: 99%
“…They based their proposal on the results obtained by chemically inducing state transitions in Synechocystis and Synechococcus PCC 7002 using 2,6-dimethoxy-1,4-benzoquinone (DMBQ), p-benzoquinone (PBQ), and 2,5-dibromo-3methyl-6-isopropyl-p-benzoquinone (DBMIB). DMBQ and PBQ accept electrons from the PQ pool (Preston and Critchley, 1988), while DBMIB inhibits cyt b 6 f activity by attaching to the Qo site (the PQH 2 binding site), preventing reoxidation of the PQ pool (Roberts and Kramer, 2001; Figure 6). These authors found that the addition of DMBQ (or PBQ) to dark-adapted cells induced an increase in F md , which they attributed to a partial transition to State I triggered by oxidation of the PQ pool.…”
Section: State Transitions Kinetics and The Redox State Of The Pq Poomentioning
confidence: 99%